PELAKSANAAN KURIKULUM JSIT (Jaringan Sekolah Islam Terpadu) DI SEKOLAH DASAR ISLAM TERPADU AL-FURQON PALEMBANG - Fajri Ismail (Universitas Muhammadiyah Ponorogo, 2018)
In this study focused on the problem of how the implementation of JSIT curriculum at Al-Furqon Palembang Integrated Islamic School and how the development of JSIT curriculum program at Al-Furqon Palembang Integrated Islamic Primary School. The purpose and usefulness of research to know the implementation of JSIT curriculum in Al-Furqon Palembang Integrated Islamic School and to know the development of JSIT curriculum at Al-Furqon Palembang Islamic Integrated School. This research is expected for the academic community to give contribution, add / enrich the study in the field of Islamic education science especially in the development of elementary school curriculum and kesesuain to learners, and can be a reference, input for educational institutions, schools studied, in order to improve quality quality education. Analysis of research data that is qualitative description by processing existing data. The JSIT curriculum system implemented at SDIT AL-Furqon consists of three curriculum combinations namely the National Curriculum, the Indonesian Integrated School of Islamic School curriculum and the Al-Furqon curriculum. The curriculum of JSIT is a curriculum pattern that integrates the National curriculum with the JSIT curriculum by leading to Islamic values. The curriculum development at SDIT Al-Furqon is directed toward the educational goals to be achieved reflected in the discipline, relating to the learning experience to achieve the goals, organizing learning experiences that describe the activities of learners interact, and related to the evaluation, learn by using the right procedures and standart.